PENGARUH KEPUASAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI SYARIAH KC LHOKSEUMAWE (Studi Seluruh Karyawan Pada PT. Bank Mandiri Syariah Kc Lhokseumawe) - Nuzul Riska; Lisa Iryani (Program Studi Administrasi Bisnis, 2021)
This study aims to explain the effect of job satisfaction and compensation on employee performance at PT Bank Mandiri Syariah Lhokseumawe. This research uses quantitative research. The population in this study was the sample in this study were employees of Bank Mandiri Syariah Lhokseumawe, amounting to 41 people. The samples in this study were employees of Bank Mandiri Syariah Lhokseumawe who were taken using a saturated sample (census). Data was collected by filling out a questionnaire, then the data was processed quantitatively. The questionnaire test consisted of data validity and reliability tests. This study uses multiple regression analysis technique with hypothesis testing using the SPSS 20 program. The results of this study indicate that job satisfaction and compensation have an effect on employee performance at PT Bank Mandiri Syariah Lhokseumawe.